La comunicación Interna para el desarrollo de la imagen Institucional del Gobierno Autónomo Descentralizado (GAD) del cantón Guaranda, año 2019 - Aguilar Sisa, Libia Consuelo (2019)
The present research has as its purpose to analyze “the internal communication for development of an institutional image of Gobierno Autónomo Descentralizado (GAD) from Guaranda city, year 2019”. We actually understand that communication is an everyday need of members who integrate the institution, and also that an adequate management of information channels, it will guarantee an effective communication in order to generate successful results, as well. Our research work is sustained on an actional Communication Direction that is responsible to manage internal communication, for which, it is proposed to apply communicative tactics and strategies in order to improve the work environment and institutional image. The employed methodology has a qualitative and quantitative position that is applied to public servants, speaking about some issues related to usage and handling of internal communication within GAD – Guaranda; this research concludes with a design of an Internal Communication Plan. Keywords: Internal Communication, institutional image, strategic plan, communicational direction